Negotiating the Water Future of Pima County, Arizona - Thuss, Michael (Arizona-Nevada Academy of Science, 1979)
From the Proceedings of the 1979 Meetings of the Arizona Section - American Water Resources Assn. and the Hydrology Section - Arizona - Nevada Academy of Science - April 13,1979, Tempe, Arizona